1991
DOI: 10.1002/kin.550230604
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric oxidation of reduced sulfur species

Abstract: The kinetics of elementary gas phase reactions involved in the oxidation of reduced sulfur species, HzS, CS2, OCS, CH3SH, CH3SCH3, and CH3SSCH3, to SOz (or other products) are reviewed. The reactions with OH and NOa which are the processes that initiate the degradation of the above compounds have been evaluated. Reactions of key intermediates, HS, HSO, CH& and CHaSO, are discussed. Whenever possible, recommendations for the rate coefficients are made and the need for further work indicated. The review has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
249
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(264 citation statements)
references
References 115 publications
7
249
0
3
Order By: Relevance
“…These results suggest different formation pathways for sulfate and nitrate. Particle-phase sulfate resulted predominantly from sulfur dioxide oxidation in the cloud free atmosphere (Tyndall and Ravishankara, 1991) and, more commonly, SO 2 conversion in clouds and fogs (Gurciullo and Pandis, 1997;Zhang et al, 1999). The preferential enrichment of nitrate in inorganic ions-rich particles was evidence of a predominant gas-phase source for nitric acid and precursors, followed by partitioning and heterogeneous/aqueous chemistry.…”
Section: Mixing State Of Biomass Burning Particles With Secondary Spementioning
confidence: 99%
“…These results suggest different formation pathways for sulfate and nitrate. Particle-phase sulfate resulted predominantly from sulfur dioxide oxidation in the cloud free atmosphere (Tyndall and Ravishankara, 1991) and, more commonly, SO 2 conversion in clouds and fogs (Gurciullo and Pandis, 1997;Zhang et al, 1999). The preferential enrichment of nitrate in inorganic ions-rich particles was evidence of a predominant gas-phase source for nitric acid and precursors, followed by partitioning and heterogeneous/aqueous chemistry.…”
Section: Mixing State Of Biomass Burning Particles With Secondary Spementioning
confidence: 99%
“…The exact mechanism of forming the sulfinyl radical from free thiol is not clear. Based on the radical reactions of organic thiols, it can be a chain-reaction,in which thiyl radical is formed first due to hydrogen abstraction by hydroxyl radical and then quickly oxidized to sulfinyl radical [53]. Molecular oxygen and NO 2 were reported to be involved in the oxidation process of thiyl radicals [6].…”
Section: Radical Attack Of Free Cysteine Residuementioning
confidence: 99%
“…Small organic sulfinyl radicals, such as HSO• and CH 3 SO•, are important products for oxidation of pollutants like H 2 S and CH 3 SH, as well as photolysis of sulfoxide, and thus play an important role in the atmospheric sulfur cycles [52][53][54]. Protein sulfinyl radicals have been detected by electron spin resonance spectroscopy for glycyl-radical enzyme system upon its exposure to molecular oxygen [55,56].…”
mentioning
confidence: 99%
“…Most reactivity studies have been carried out with mixing ratios of CS 2 and .OH in large excess of ambient levels. It has been suggested that oxidation with .OH in air may also involve two oxygen molecules [Tyndall and Ravishankara, 1991 Photon flux, necessary lbr quantum yield measurements, was quantified with ferrioxalate actinometry [Hatchard and Parker, 1956;Parker, 1953] UV-VIS spectra were taken with either an IBM 9420 UV-VIS spectrophotometer or a Hewlett Packard 8452A diode army spectrometer. Quantum yields measurements employed UV-VIS analysis, and a 2.5 cm diameter, 10 cm length Pyrex cell fitted with quartz windows and a Teflon stopcock.…”
Section: With the Diumally Averaged Value For [Oh] Taken As 8x105mentioning
confidence: 99%